2023
DOI: 10.1149/1945-7111/acb4be
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of Photoelectrochemical Oxygen Evolution Sites in TiO2 Nanotube Array Electrodes by PbO2 Deposition Method

Abstract: TiO2 nanotube (TNT) photoanodes exhibit activity and stability for the oxygen evolution reaction (OER) by photoelectrochemical water oxidation. However, the location of the OER site by the photogenerated holes has not been clarified for the TNT photoanodes, unlike well-studied macrocrystalline photocatalysts. In this study, we performed reactions of TNT photoanodes in a 0.1 M Pb(NO3)2 under UV irradiation. The photoelectrochemically deposited PbO2 particles were observed through scanning electron microscopy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Tsampas et al [17,18] and Amano et al, [7,9,19] separately reported the preparation of TiO 2 nanotube arrays (TNTAs) on 3D porous Ti-felt substrate by electrochemical anodization and subsequent annealing in air/O 2 , as depicted in Figure 3A. Tsampas et al conducted anodization at 30 V using the electrolyte (ethylene glycol containing 0.3 wt % ammonium fluoride and 2 vol % water) pre-aged with a dummy sample for 10 h to minimize cracks and the detachment of TNTA.…”
Section: Tio 2 On Feltmentioning
confidence: 98%
See 3 more Smart Citations
“…Tsampas et al [17,18] and Amano et al, [7,9,19] separately reported the preparation of TiO 2 nanotube arrays (TNTAs) on 3D porous Ti-felt substrate by electrochemical anodization and subsequent annealing in air/O 2 , as depicted in Figure 3A. Tsampas et al conducted anodization at 30 V using the electrolyte (ethylene glycol containing 0.3 wt % ammonium fluoride and 2 vol % water) pre-aged with a dummy sample for 10 h to minimize cracks and the detachment of TNTA.…”
Section: Tio 2 On Feltmentioning
confidence: 98%
“…[5,6] Several porous photoanodes (ntype TiO 2 , WO 3 , BiVO 4 , Fe 2 O 3 , and SrTiO 3 ) and photocathodes (ptype CuInS 2 and Cu 2 O) have been prepared on porous felt substrates composed of carbon and titanium microfibers. [4][5][6][7][8][9][10][11][12][13] Carbon microfibers could be oxidatively decomposed during thermal treatments and photoanodic reactions. In contrast, titanium microfibers have better tolerance under oxidative conditions compared with carbon microfibers.…”
Section: Microfiber-felt Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ti felt was used as the conductive substrate for the gasdiffusion photoanodes. The WO 3 electrode was prepared by dip coating with an aqueous solution of (NH 4 ) 6 H 2 W 12 O 40 and polyethylene glycol; the electrode was then calcined at 923 K for 2 h. 7,28,40 The TiO 2 electrode was prepared by the anodization of Ti felt in ethylene glycol with 0.25 wt% NH 4 F and 10 vol% H 2 O at 50 V for 3 h. 29,41,42 The anodized Ti felt was calcined at 823 K for 1 h to crystallize into anatase TiO 2 . The photoanodes were modified using a Nafion ionomer dispersion (Sigma-Aldrich).…”
Section: Preparation Of Photoanodesmentioning
confidence: 99%